Experimental Investigation of Photovoltaic Partial Shading Losses under Different Operation Conditions - Numan, Ali H.; Dawood, Zahraa Salman; Hussein, Hashim A. (Al-Nahrain Journal for Engineering Sciences, 2020)
The partial shading conditions have a significant effect on the performance of Photovoltaic system and the ability of delivering energy. In this study, the impact of different partial shading on the mono crystalline (88W) PV module performance was investigated in this study. Horizontal string, vertical string, and single cell shading at different percentage of shading area have been studied. It is found that the horizontal string shading is more severe on the efficiency of the PV panel. In contrast, the efficiency of PV panel with cellular and vertical cell shading was less during the tests. The experimental results showed that the power losses were 99.8%, 66% and 56.8 % for horizontal, cellular and vertical shading respectively via applied non transparent material as shading element by 100% of shading area at 500 W/m2. Moreover, transparent material used to shade whole module horizontally, different shading area and different radiation level applied to find electrical characteristics of the module under these conditions. The results show that at 800W/m2 of irradiation levels and no shading condition the power was 68.6W, by increase shading area by 20% in each step, the power reducing by 44.94, 47.58, 49.42, 50.57 and 52.4% in compared with their initial value at no shading condition.